THE ESSENTIAL ROLE OF PHYSIOTHERAPY IN PROFESSIONAL FOOTBALL - da Fonseca, Giulliana Iafrate (Revista Sistemática, 2024)
The role of physiotherapists in professional football is critical for both the physical recovery of athletes and the implementation of strategies that promote injury prevention and enhance performance. With a comprehensive understanding of biomechanics and movement principles, physiotherapists can assess players’ performance and work closely with coaching staff to devise effective game tactics. Their expertise enables them to identify movement patterns and areas of stress that can lead to injuries, ultimately helping to minimize these risks. Education plays a vital part in the physiotherapist's responsibilities, as they teach athletes about health maintenance and the significance of injury prevention. This educational component is essential for ensuring that players can sustain a long and successful sports career. Despite progress in prevention and rehabilitation practices, studies reveal persistent gaps between clinical practice and scientific evidence. Increased regulation of the profession, coupled with a multidisciplinary approach that incorporates psychological support, emphasizes the growing importance of physiotherapy within football. Moreover, recognizing the psychological factors that influence recovery and utilizing evidence-based protocols are vital for optimizing rehabilitation outcomes. The physiotherapist’s influence extends beyond physical recovery; they are integral in fostering the overall health and well-being of athletes, which significantly impacts team performance. Moving forward, the field of physiotherapy in football must prioritize continuous professional development, the adoption of innovative practices, and the establishment of an environment that values both the physical and mental health of players.